PENGARUH MOBILISASI PROGRESIF TERHADAP STATUS HEMODINAMIK PASIEN DI RUANG ICU : LITERATURE REVIEW - Apriyani Apriyani; Sri Tirtayanti (Masker Medika, 2021)
Background : Progressive mobilization is one way of movement for monitoring the hemodynamic status of patients in the ICU. Hemodinamic instability can also be an obstacle to progressive mobilization. Recovery of hemodynamic status Could be conducted through nursing interventions by providing physical activity, namely progressive mobilization using of Head to Bed (HOB) and Range of Motion (ROM) movements given 2-3 times a day for 15-20 minutes each time. Objective : To determine the effect of progressive mobilization on the hemodynamic status of patients in the ICU. Research Methods : This study used a literature review as an approach using PubMed and Google Scholar as an electronic database, whereas year range 2016-2020 was the inclusion criteria. Several keyword were used to search the articles, those were progressive mobilization, hemodynamic status and ICU patients. Result : Four journals found that the phenomenon had been explained by giving progressive mobilization of patients in the ICU to monitoring the hemodynamic status. Conclusion : It can be concluded that progressive mobilization might improve the hemodynamic status of patients in the ICU.